THE CONSTRUCTION OF HERSELF: THE PRESENCE OF THE FIGURE OF KIKI OF MONTPARNASSE IN THE VANGUARDIST SCENARIO (Palíndromo, 2018)
The scope of this article is to trace some points of the construction of the figure of Alice Prin - better known as Kiki of Montparnasse - in relation to the well-known modernist male artists during the interwar period (1920-1930), and also the invention of herself observed in the whole of Kiki’s artistic production. In this sense, we seek, on the one hand, to understand the ambience of this world that portrayed her and, on the other hand, to counteract this context, we dwell on the peculiar feminine participation of Kiki and the writings of her diary.
Keywords: female participation; Kiki de Montparnasse; modernism; avant-garde scene